Food safety education for PKK cadres in Mancilan Village, Jombang Regency through borax and formalin detection training - Anggi Indah Yuliana; Mohamad Nasirudin; Siti Nur Qomariyah (Universitas Muhammadiyah Magelang, 2023)
We need to exercise caution regarding the distribution of instant foods that may potentially contain borax and formaldehyde in order to minimize the risk of health issues within families. However, the majority of people, including the residents of Mancilan Village in Mojoagung District, Jombang Regency, are not yet knowledgeable about how to identify food products that may be tainted with borax or formaldehyde. Therefore, the objective of this community service initiative is to enhance the understanding of Mancilan Village PKK cadres regarding the hazards posed by borax and formaldehyde to family health. Additionally, it aims to enhance and develop the cadres' skills in detecting borax and formaldehyde content in food items. The methods employed in this initiative encompass workshops, demonstrations, simulations, and focus group discussions, involving 30 participants. The socialization activities have had a significant impact on improving the cadres' knowledge concerning additional food ingredients (an increase of 21.6 points), the characteristics and risks associated with borax (an increase of 20 points), and the characteristics and dangers of formaldehyde (an increase of 23.3 points). The training activities have qualitatively succeeded in enhancing the skills for the detection of borax and formalin contamination.